All-Russian scientific and practical conference on developing project-based training for the creative economy / Всероссийская научно-практическая конференция «Развитие проектного подхода к подготовке специалистов для креативной экономики» - YULIA M. BELOZEROVA / Ю.М.БЕЛОЗЕРОВА (Наука телевидения)
This review covers the All-Russian scientific and practical conference, Developing Project-Based Training for the Creative Economy, held October 25, 2024, at the Moscow State Institute of Culture. The conference focused on cultivating creative competencies—including creative thinking, communication, and problem-solving—in future culture and arts professionals. It also explored fostering creative approaches in training for non-creative fields like engineering, medicine, law, and accounting. Presentations addressed the formation and management of a communicative culture for effective interdisciplinary teamwork, the role of environmental education and sustainable development, and the integration of creative projects aimed at fostering social responsibility among students into educational programs. Discussions included educational game design and a showcase of best practices implemented in Russian higher education’s creative industries. Conference participants shared experiences and practical recommendations for the implementation of innovative teaching methods. A key task of the conference was to determine the most effective programs and approaches for training faculty to nurture students’ creative potential.